Negotiating coherence through meeting spaces in practicum - Marit Ulvik; Liv Eide; Ingrid Helleve; Edel Karin Kvam (Social Sciences and Humanities Open, 2023)
Teacher education takes place in two distinct cultures: schools and higher education institutions. The differences between these cultures make interaction between them challenging and often described as disconnected. There is a call for coherence. This interview study explores how meeting spaces during practicum can enhance coherence between university coursework and fieldwork in teacher education seen from the perspectives of student teachers, school-based and university-based teacher educators in Norwegian secondary school teacher education. The findings suggest that creating coherence requires meeting spaces that encourage student teachers’ reflection and are characterised by mutual respect where various perspectives can complement and challenge each other.